Case Report: Cranial Vault Reduction Cranioplasty for Severe Hydrocephalus - Suryaningtyas, Wihasto; Parenrengi, Muhammad Arifin (Folia Medica Indonesiana, 2020)
Extreme hydrocephalic macrocephaly is still encountered in developing countries due to delayed treatment, rapidly progressing hydrocephalus and family socioeconomic problems. Reduction cranioplasty was used with several techniques to address the issue. The study aimed to determine the safety and feasibility of barrel-stave technique for reducing the size of extreme hydrocephalic macrocephaly. Three post-diversion patients underwent surgical reconstruction. Children with head circumference more or equal to two standard deviation above mean on given age, no active wound at the area of surgery, presentation of sufficient